Translation of Pronouns and Deictic Positioning in the Thai Prime Minister’s Weekly Addresses (KEMANUSIAAN The Asian Journal of Humanities, 2022)
This study investigates the translation of the weekly Thai prime ministerial addresses, focusing on pronouns and deictic positioning. The English translation is considered a new feature of this political genre, with implications for Thailand’s political situation. The study analyses Prayut Chan-o-cha’s weekly addresses using Munday’s pronouns and deixis categorisation based on the interpersonal concept in systemic functional linguistics. The central concerns are how the premier used Thai pronouns and positioned the addressees in his speeches and if their translation properly represents them. The findings reveal that the prime minister’s (PM) selection of pronouns defines his addressees into distant and proximate, positive and negative groups. However, his pronoun use is ambivalent and slippery. The translation of his pronoun use causes the obligatory shifts in the target text because of the structural differences between Thai and English. There is a tendency for explicitation of the PM’s deictic positioning due to the re-insertion of the missing pronouns. In rendering the PM’s temporal deixis into English, the translator managed to connect his imagined glorious past of Thailand with its hopeful future. These explicit time links evoke a nationalistic image and allude to Thailand’s recent political turmoil.